Integrative analysis of DNA methylation and inflammatory protein biomarkers in hypertension - Zhu, Min; Zhang, Jin; Ma, Jing; Tang, Xiaofeng; Wang, Yan; Zhu, Dingliang (Frontiers in Immunology, 2026)
Background and objectiveTo investigate the relationship between inflammation and hypertension by comparing epigenetic and serum biomarkers of inflammation and their association with target organ damage (TOD).MethodsThe epigenome-wide methylation profiles of peripheral leukocyte DNA from 176 patients with hypertension were analyzed using Illumina Infinium Methylation EPIC BeadChips. The commercially available Olink® Target 96 Inflammation panels were utilized to evaluate markers associated with inflammation. We identified CpG-protein association protein quantitative trait methylation loci (pQTMs) using mixed linear regression, adjusting for potential confounders. The possible roles of the discovered pQTMs were ascertained by Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) pathway analyses. The association between pQTMs and TOD was also analyzed.ResultsIn our analysis, we found 771 significant associations across 11 biomarkers, with a false discovery rate (FDR) of less than 0.05. Lambda estimates ranged from 0.847 to 1.202. Among these, 39 pQTMs showed an association with urine albumin-creatinine ratio, while 82 pQTMs showed an association with carotid intima-media thickness.ConclusionOur findings contribute to the understanding of inflammatory biomarkers associated with alterations in DNA methylation in hypertension. However, these results will need to be validated in future studies.